Role of diet in the aetiopathogenesis of acne - Kowalska, Hanna; Sysa-Jędrzejowska, Anna; Woźniacka, Anna (Dermatology Review/Przegląd Dermatologiczny, 2018)
Acne vulgaris is one of the most common dermatoses among teenagers and young adults. Recent data from multi-centre studies indicate that the average prevalence of acne in the 15–24 age group is 58% in Europe and 42% in Poland. The aetiopathogenesis of acne is complex, involving inflammatory, immunological, genetic, hormonal and environmental factors (cosmetics, medications and the so-called Western pattern diet). Recent survey studies show that diet is commonly considered to be an acne-exacerbating factor. As many as 70% of respondents report introducing various dietary modifications to improve their skin condition. However, the link between diet and acne is controversial and studies to date are insufficient to formulate any evidence-based dietary guidelines for acne prevention and treatment. The best documented finding is the adverse effect of milk and foods with a high glycaemic index on the skin of patients with acne vulgaris. Although the role of chocolate (cocoa) consumption is controversial, the most recent randomized trials point towards its potential pathogenetic involvement in inducing acne exacerbation.